2006
DOI: 10.1039/b511146c
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption kinetics of l-glutathione on gold and structural changes during self-assembly: an in situATR-IR and QCM study

Abstract: The adsorption of L-glutathione (g-Glu-Cys-Gly) from ethanol on gold surfaces was studied in situ by both attenuated total reflection infrared (ATR-IR) spectroscopy and using a quartz crystal microbalance (QCM). The molecule is firmly anchored to the gold surface through the thiol group. Different IR signals of adsorbed L-glutathione, notably the amide I and n(-COOH), show significantly different behavior with time, which reveals that their increase is not related to adsorption (mass uptake) alone. This indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
41
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 25 publications
1
41
0
Order By: Relevance
“…A particularly common occurrence is what appears to be a two-rate type process, where a fast initial adsorption step is followed by a slower stage of adsorption before equilibrium is reached. This is generally not explained by any of the 'traditional' isotherms listed above, and so a range of new models have arisen in the last few decades in an attempt to provide a physical rationalization for the behavior seen [6][7][8][9][10][11][12][13]. Typically, the two-rate adsorption behavior can be a result of four possibilities (or a combination of them) -two-sites with different energies [14][15][16][17][18], two species with different adsorption rate constants (or diffusion coefficients) [19], rearrangement of adsorbed molecules on the surface [20][21][22][23] or bilayer adsorption [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 97%
“…A particularly common occurrence is what appears to be a two-rate type process, where a fast initial adsorption step is followed by a slower stage of adsorption before equilibrium is reached. This is generally not explained by any of the 'traditional' isotherms listed above, and so a range of new models have arisen in the last few decades in an attempt to provide a physical rationalization for the behavior seen [6][7][8][9][10][11][12][13]. Typically, the two-rate adsorption behavior can be a result of four possibilities (or a combination of them) -two-sites with different energies [14][15][16][17][18], two species with different adsorption rate constants (or diffusion coefficients) [19], rearrangement of adsorbed molecules on the surface [20][21][22][23] or bilayer adsorption [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 97%
“…It was demonstrated that GSSG assumes a head-to-tail conformation in solution at neutral pH. Using attenuated total reflectance infrared spectroscopy and quartz crystal microbalance analysis, Bieri et al [18] found that the protonation-deprotonation equilibrium was sensitive to external stimuli, such as the presence of dissolved L-glutathione molecules. Lyon and Atkins [19] studied the self-assembly and gelation of oxidized glutathione in organic solvents.…”
Section: Introductionmentioning
confidence: 98%
“…Research has been focused on GSH and GSSG in recent years [17][18][19][20][21][22][23][24][25][26][27][28]. Molecular dynamics (MD) simulations and NMR techniques are often used to study the structures and properties of biochemical molecules in solutions [17][18][19][20][21]. Potentiometric and NMR spectroscopic measurements were performed by Krezel et al [17] to study protonation and Zn(II) binding properties of GSSG and a series of nine analogs with C-terminal modifications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…GSH, a tripeptide from glycine, cysteine and glutamate, is the most abundant non-protein thiol-bearing molecule of mammalian cells and is involved in many physiological processes [15][16][17]. GSH is known to interact with ions and heavy metals, and is capable to organize on gold surfaces as self assembled monolayers (SAMs) [18]. SAMs serve as sensitive sensing layer for cantilever based sensors.…”
Section: Introductionmentioning
confidence: 99%